The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/jcm8040488
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Creatine Supplementation on Aging Muscle and Bone: Focus on Falls Prevention and Inflammation

Abstract: Sarcopenia, defined as the age-related decrease in muscle mass, strength and physical performance, is associated with reduced bone mass and elevated low-grade inflammation. From a healthy aging perspective, interventions which overcome sarcopenia are clinically relevant. Accumulating evidence suggests that exogenous creatine supplementation has the potential to increase aging muscle mass, muscle performance, and decrease the risk of falls and possibly attenuate inflammation and loss of bone mineral. Therefore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
72
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(82 citation statements)
references
References 101 publications
(138 reference statements)
1
72
0
2
Order By: Relevance
“…Higher doses of calcium associate with greater bone mineral density too, and given bone is the largest depot of calcium in the body, it seems imperative to maintain sufficient intake with age, despite the debate of this micronutrient in lowering fracture risk . Creatine is another nutrient that has consistently been shown to enhance muscle mass, strength, and function and may be a promising strategy to preserve bone microarchitecture and strength, although investigations have largely been conducted in healthy older adults.…”
Section: Translational Geroscience and Osteosarcopeniamentioning
confidence: 99%
“…Higher doses of calcium associate with greater bone mineral density too, and given bone is the largest depot of calcium in the body, it seems imperative to maintain sufficient intake with age, despite the debate of this micronutrient in lowering fracture risk . Creatine is another nutrient that has consistently been shown to enhance muscle mass, strength, and function and may be a promising strategy to preserve bone microarchitecture and strength, although investigations have largely been conducted in healthy older adults.…”
Section: Translational Geroscience and Osteosarcopeniamentioning
confidence: 99%
“…Separately, creatine is essential for muscle ATP production and has been commonly ingested to enhance anabolic response to exercise. Multiple studies have presented some evidence that creatine treatment, in combination with resistance training, enhances gains in muscle mass and strength following exercise beyond what is attainable with resistance exercise alone (Candow et al, 2019). The benefit of creatine therapy alone without resistance training remains unclear; some have suggested that creatine ingestion improves lean muscle mass in the elderly (Gotshalk et al, 2002), whereas others have observed no benefit in muscle mass or strength with creatine administration (Lobo et al, 2015;Baker et al, 2016;Chami and Candow, 2019).…”
Section: Nutritional Supplementationmentioning
confidence: 99%
“…Creatine is an organic compound naturally produced in the body from reactions involving the amino acids arginine, glycine and methionine in the kidneys and liver or consumed in the diet primarily from red meat, poultry, seafood [ 1 ] or supplementation practices. There is substantial evidence that creatine supplementation and resistance training increases muscle mass and performance (i.e., strength) more than placebo and resistance training, possibly by influencing phosphate metabolism, cellular hydration status, calcium and protein kinetics, glycogen content, satellite cells, growth factors, inflammation and oxidative stress (for reviews see [ 2 , 3 , 4 , 5 , 6 ]).…”
Section: Introductionmentioning
confidence: 99%